O novo ensino médio: adaptações e resistências na percepção dos professores da Fundação Instituto de Educação de Barueri (FIEB) - Santos, Lilian da Silva (2024)
This work seeks to analyze the impacts generated by the reform of Secondary Education qualified by Law No. 13,415/2017, in the process of curricular reorganization of the schools of the Fundação Instituto de Educação de Barueri (FIEB). To this end, research was developed in three dimensions: documentary, bibliographic and empirical. Documentary research was dedicated to understanding the guidelines that support the proposition of systematized change policies for Secondary Education, as proposed in educational documents and multilateral agencies such as the World Bank and OECD, and the legal regulations that promoted debates regarding the curricular flexibility and consolidation of General Competencies presupposed in the National Curricular Common Base (BNCC). The bibliographical research, focused on the scientific production of categories such as the reform of Secondary Education, the BNCC and the Training Itineraries, delimited in the literature review, studies of the main theoretical references on contemporary trends in reconfiguring curricula in Basic Education, with an emphasis in the New High School. The empirical research sought, through semi-structured interviews with teachers from FIEB in Barueri, a municipality in the metropolitan region of São Paulo, to analyze what perception teachers have of the reform of Secondary Education, qualified by Law No. 13,415/2017, in the process of curricular (re)organization of the Foundation's schools, in order to understand the possible impacts on their pedagogical praxis. The study sought to demonstrate how the current reform of Brazilian Secondary Education, materialized by Law No. 13,415/2017, is one of these examples of how, historically, Brazilian education is tensioned by guidelines and guidelines that create biases to adjust the training of students. students in the direction of model conceptions of the society they live in, expanded by speeches and speeches, by existential paradigms and by market narratives among which the young person is enamored with the vision of the future through the discussion regarding their formative processes.